Paradoxical effects of lipolysis on the lipid oxidation in meat and meat products - Nantawat Tatiyaborworntham; Fatih Oz; Mark P. Richards; Haizhou Wu (Food Chemistry: X, 2022)
Lipolysis in meat and meat products is a phenomenon involving hydrolysis of lipids, notably via enzymatic catalysis that takes place even postmortem. During refrigerated and frozen storage of meat, in particular fish, endogenous lipolytic enzymes actively degrade triacylglycerols and phospholipids resulting in accumulation of free fatty acids and other hydrolytic products. A classical conjecture suggests that lipolysis enhances lipid oxidation which is involved in quality deterioration of fresh meat and, to some degrees, flavor development of certain meat products. Recent studies (<5 years) have shown that under some circumstances, lipolysis of certain lipolytic enzymes can inhibit lipid oxidation in muscle models, which provides more insight in lipid oxidation mechanisms in muscle matrices as well as implies potential strategies for improving meat quality. This review will discuss such paradoxical effects and potential mechanisms of lipolysis on lipid oxidation in meat and meat products.